Aboveground-Belowground Community Ecology (Ecological Studies, Analysis and Synthesis,, 2018)
Researchers now recognize that above- and belowground communities are indirectly linked to one another, often by plant-mediated mechanisms. To date, however, there has been no single multi-authored edited volume on the subject. This book remedies that gap, and offers state-of-the art insights into basic and applied research on aboveground-belowground interactions and their functional consequences. Drawing on a diverse pool of global expertise, the authors present diverse approaches that span a range of scales and levels of complexity. The respective chapters provide in-depth information on the current state of research, and outline future prospects in the field of aboveground-belowground community ecology. In particular, the book's goal is to expand readers' knowledge of the evolutionary, community and ecosystem consequences of aboveground-belowground interactions, making it essential reading for all biologists, graduate students and advanced undergraduates working in this rapidly expanding field. It touches on multiple research fields including ecology, botany, zoology, entomology, microbiology and the related applied areas of biodiversity management and conservation.